Academic Accreditation From The point Of view The Teaching Staff Of Iraqi Expatriates And Its Impact On Strategic Performance Of Institutions Of Higher Education - Field Research - حافظ, عبد الناصر علك; جميل, اية طالب (Journal of Economics and Administrative Sciences, 2016)
Abstract       The Research Includes Two Variables : First , Academic Accreditation with his dimensions ( Educational Context , Educational Inputs , Educational Process , Educational Outputs , Feedback ) , And The Second : Strategic Performance With His dimensions ( Financing , Satisfaction Stakeholders , Internal Processes , Learning And Growth ) , The Research Highlights On The Academic Accreditation System Which Is Considered A Major And Important Systems Can Through Which Administration Of Activities And Programs Institutions Of Higher Education , As This research aims to determine his relationship And The Extent Of Its Effect In The Strategic Performance , And It Includes The Research Community Iraqis Teaching Staff Expatriates Working In International Universities It Was The Opinion Of A Sample Of ( 55 ) Teaching Staff , The Questionnaire Was Used As A Key Tool In Collecting Data And Information  , And To Data Analysis Was Used The Statistical Program The  ( SPSS ) , The Search Results Showed That The Universities Which Works At  Faculty Iraqi Expatriates  Applying Academic Accreditation System Results Also Showed  Existence Correlation Relationship Between The Dimensions Of Academic Accreditation, Strategic Performance As Well As Having The Effect To The Dimensions Of Academic Accreditation In Strategic Performance , And Offers The Search A Set Of Recommendations Based On The Conclusions That Have Been Reached Including The Need To Take Advantage Of Academic Accreditation System And Work To Develop It Constantly  And Also The Need To Continue The Measurement Of Strategic Performance In Order To Identify The Strengths And Working On Promotion And Identify Weaknesses And Work To Avoid Them